Development of Video Clips of Childrens Song about Food Chain to Increase Students’ IPAS Learning Outcome - Wijaya, Bijak Samuel; Andaryani, Eka Titi (Jurnal Pijar Mipa, 2025)
Abstract concepts in learning materials often become a challenge for students in understanding the concepts of the material, such as the food chain material in IPAS learning. This research developed audiovisual media in the form of video clips of children's songs, which were developed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, with the aim of increasing students' understanding as measured by increasing their learning outcomes. The stages of this research include needs analysis, media design, product development, implementation, and evaluation of media effectiveness. Children's song video clip media was proven suitable for use after going through a validity test with a score of 92.1% from material experts and 91.25% from media experts. The increase in learning outcomes is evidenced by the increase in pretest and posttest results, with an average of 73.57 to 84.29 in the small group and an average of 70.25 to 80.75 in the large group. A positive response was also obtained in this study, with a score of 97.5% from the teacher response questionnaire and 90.91% from the student response questionnaire. In addition, this study was considered successful because the t-test obtained a Sig. (2-tailed) or significance value of 0.000 in both small and large groups, which means that the pretest and posttest were significant, because the significance value was less than 0.05, then in the N-Gain test, a value of 0.4170 was obtained in the small group and 0.3617 in the large group. Both scores indicate that the effectiveness of learning is in the medium category, because the N-Gain test value obtained in both small and large groups is in the range of 0.3-0.7. The results of this research conclude that the combination of audio media in the form of songs and visual media in the form of video clips can be a solution in overcoming low levels of understanding and improving learning outcomes in the learning process, especially for food chain material.